Experimental investigation of the role of komatiite-peridotite interaction in generating silica enrichment in the cratonic lithosphere - Tomlinson, Emma (Cambridge University Press, 2026)
Silica enrichment in cratonic peridotites, expressed as high modal contents of orthopyroxene is a common yet enigmatic feature of Archean lithospheric mantle. Less widely recognised, silica depletion, expressed as high olivine content is also present in some locations. Although high-pressure melting alone cannot account for the full range of observed silica contents, open-system interaction between mantle melts and lithospheric peridotite offers a viable alternative. We present results from high-pressure (5 GPa), high-temperature (1600–1690°C) multi-anvil experiments designed to investigate the reaction between Al-depleted komatiitic melts and both fertile and moderately depleted peridotite. Using hybrid and reaction-couple experimental configurations, we track mineralogical and compositional changes across controlled thermal gradients within the experimental capsules. Modal and compositional data reveal a two-stage reaction process. Stage 1 involves high-temperature olivine precipitation from primitive Al-depleted komatiitic melts interacting with peridotite to produce olivine-rich residues with high MgO/SiO2 and low Al2O3/ SiO2. As a result of olivine removal, the coexisting melt becomes enriched in SiO2. In stage 2, the now silica-enriched komatiite melt reacts with residual olivine (±clinopyroxene and garnet) to form orthopyroxene at moderate temperature, increasing the bulk SiO2 content. Residue bulk compositions from olivine-rich zones resemble high-Mg# garnet dunites from Archean lithosphere, whereas orthopyroxene-rich zones are analogues to natural silica-rich cratonic peridotites. Coexisting melts evolve from komatiitic toward picritic compositions as the reaction progresses. We infer that reactive porous flow of komatiitic melts through depleted lithosphere can simultaneously generate silica-depleted and silica-enriched, refractory residues and diversify melt compositions, providing a process-based framework for the chemical and textural diversity of cratonic mantle.
PUBLISHED
Keywords: komatiite–peridotite reaction; orthopyroxene enrichment; cratonic lithospheric mantle; high-pressure experimental petrology; GEOLOGY; Geochemistry; Petrology, Minerology, Geochemistry